Open‐label, dose‐titration tolerability study of atomoxetine hydrochloride in Korean, Chinese, and Taiwanese adults with attention‐deficit/hyperactivity disorder. (23rd July 2012) - Takahashi, Michihiro; Goto, Taro; Takita, Yasushi; Chung, Sang‐Keun; Wang, Yufeng; Gau, Susan Shur‐Fen
Abstract Introduction The primary objective of this study was to assess the overall safety and tolerability of atomoxetine in Korean, Chinese, and Taiwanese adults with attention‐deficit/hyperactivity disorder (ADHD). Methods A total of 44 patients aged ≥18 years who met the Conners' Adult ADHD Diagnostic Interview for DSM‐IV diagnostic criteria for ADHD were enrolled from China, Korea, and Taiwan. In this open‐label, dose‐escalation study, patients received atomoxetine orally once daily over a period of eight weeks, starting at 40 mg/day (one week) up to a maximum dosage of 120 mg/day. Tolerability was evaluated by rate of discontinuation due to adverse events. Safety was assessed by recording all adverse events, laboratory tests, vital signs, and electrocardiograms. ADHD symptoms were evaluated by the Conners' Adult ADHD Rating Scale‐Investigator Rated: Screening Version (CAARS‐Inv:SV) for efficacy assessment. Results Thirty‐four patients (77.3%) completed the study. Atomoxetine was well tolerated with a discontinuation rate of 2.3% (1/44) due to adverse events. The most commonly reported adverse events were nausea, dizziness, and somnolence. The mean change from baseline to endpoint in CAARS‐Inv:SV total ADHD symptom score was −12.5 (P < 0.001). A significant reduction in the CAARS‐Inv:SV subscales (inattentive, hyperactive/impulsive, and ADHD index score, P < 0.001) was observed. Discussion This is the first atomoxetine clinical trial in adult patients with ADHD in China, Korea, and Taiwan. Atomoxetine was well tolerated in doses of up to 120 mg/day with no unknown safety concerns.